An Examination of Stroke-Related Knowledge in Male Stroke Survivors Living in the South Carolina Stroke Belt. (November 2014) - Ellis, Charles
Racial differences have been observed in stroke-related knowledge and knowledge of specific stroke risk factors and stroke prevention practices. Using data from 134 male stroke survivors, racial differences in overall knowledge, risk factor knowledge, and stroke prevention practices were examined using the Stroke Knowledge Test. Knowledge that diabetes doubles ones risk of stroke was present in 48% of the participants, while knowledge of aspirin in the prevention of stroke by stopping blood clot formation was reported in 83% of the participants. Findings indicate participants were knowledgeable that obesity increased risk of stroke (71%) and high blood pressure was the most important stroke risk factor (70%). Participants indicated knowledge that diet, exercise, and controlling blood pressure and cholesterol reduces risk of stroke (86%). In regression models, there were no significant race differences in overall stroke knowledge or the odds of knowledge of information related to stroke risk factors and stroke prevention practices after adjusting for age, education, and marital status. Although stroke-related knowledge did not differ by race, stroke survivors exhibited gaps in stroke knowledge particularly of knowledge of common risk factors. These factors should be considered in approaches to improve stroke-related knowledge in all stroke survivors.